2012
DOI: 10.1073/pnas.1201516109
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based therapy in an in vivo microRNA-155 (miR-155)-dependent mouse model of lymphoma

Abstract: is an oncogenic microRNA that regulates several pathways involved in cell division and immunoregulation. It is overexpressed in numerous cancers, is often correlated with poor prognosis, and is thus a key target for future therapies. In this work we show that overexpression of miR-155 in lymphoid tissues results in disseminated lymphoma characterized by a clonal, transplantable pre-B-cell population of neoplastic lymphocytes. Withdrawal of miR-155 in mice with established disease results in rapid regression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
378
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(383 citation statements)
references
References 68 publications
5
378
0
Order By: Relevance
“…More interestingly transplanting ASO expressing MDA-MB-157 cells in mice inhibited growth of tumor . For enhancing the delivery and distribution of antisense against miR-155, polymeric nanoparticles encapsulated antisense peptide nucleic acids have been used (Babar et al, 2012).…”
Section: Mir-155: In Vitro Studiesmentioning
confidence: 99%
“…More interestingly transplanting ASO expressing MDA-MB-157 cells in mice inhibited growth of tumor . For enhancing the delivery and distribution of antisense against miR-155, polymeric nanoparticles encapsulated antisense peptide nucleic acids have been used (Babar et al, 2012).…”
Section: Mir-155: In Vitro Studiesmentioning
confidence: 99%
“…Furthermore, the strategy to knockdown miR-155 has been previously investigated for the control of cancer progression (24). Previous studies have demonstrated that knockdown of miR-155 in mice resulted in rapid regression of lymphadenopathy, in part due to apoptosis of the malignant lymphocytes (25). In addition, systemic delivery of antisense peptide nucleic acids against miR-155 that were encapsulated in unique polymer nanoparticles inhibited miR-155 and retarded the growth of pre-B-cell tumors in vivo, suggesting a potential therapeutic option for the treatment of lymphoma/leukemia (25).…”
Section: A B D Cmentioning
confidence: 99%
“…Differential expression of ncRNAs in malignant tissues compared with normal tissues can be exploited as potential therapeutic targets for cancer therapy or as biomarkers used for diagnosis, prediction of patient outcome, or monitoring the effectiveness of cancer therapeutics [11]. In recent years serious attempts have been made to effectively deliver ncRNA into tumors in animal models [12][13][14].…”
Section: A Research In Ncrna Biologymentioning
confidence: 99%